Smartphone applications to make project results available to private sector extension providers and farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Hersheys, ECOM, Touton and Olam comissioned the development of a smartphone app for cocoa producers in Ghana combining climate exposure maps and recommended CSA practices by gradient. A Stepwise app was developed for use by impact partner extension workers including Hanns R. Neumann Stiftung and Olam.